Dynamic Monopolist's Behavio and Consumer Learning - Carlo Scarpa (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1988)
This paper studies the optimal behavior of a monopolist in the presence of asymmetric information cencerning the characteristics of the good he produces.
Keywords: 330